2006
DOI: 10.1177/000312240607100503
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Protest Diffusion: Movement Organizations, Social Networks, and News Media in the 1960 Sit-Ins

Abstract: The wave of sit-ins that swept through the American South in the spring of 1960 transformed the struggle for racial equality. This episode is widely cited in the literature on social movements, but the debate over its explanation remains unresolved?partly because previous research has relied on case studies of a few large cities. The authors use event-history analysis to trace the diffusion of sit-ins throughout the South and to compare cities where sit-ins occurred with the majority of cities where they did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
182
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(193 citation statements)
references
References 58 publications
6
182
0
5
Order By: Relevance
“…13 The role of international and domestic civil society organizations, both with and without a human rights focus, in mobilizing domestic non-violent protest is also well established in the protest literature on the United States. For example, Heaney and Rojas surveyed 5,410 demonstrators in anti-war protests in the United States and found that the majority of protesters were connected to at least one international or 9 Andrews and Biggs 2006;Haines 1984. 10 Kriesi 1996.…”
Section: Existing Perspectives On Hros and Non-violent Protest Mobilimentioning
confidence: 99%
“…13 The role of international and domestic civil society organizations, both with and without a human rights focus, in mobilizing domestic non-violent protest is also well established in the protest literature on the United States. For example, Heaney and Rojas surveyed 5,410 demonstrators in anti-war protests in the United States and found that the majority of protesters were connected to at least one international or 9 Andrews and Biggs 2006;Haines 1984. 10 Kriesi 1996.…”
Section: Existing Perspectives On Hros and Non-violent Protest Mobilimentioning
confidence: 99%
“…Sometimes they do, as in Argentina in 2001 (Borland and Sutton 2005), but often they do not, for example, in the Faroe Islands and Finland in the early 1990s. If efforts to generalize about the societal conditions triggering large-scale protests and revolts constitute a major topic in social movement research (Andrews and Biggs 2006;Davies 1962;McAdam, McCarthy, and Zald 1996;Opp and Gern 1993), the protests in Iceland provide an opportunity to study what happens when an economic crisis triggers large-scale public protest, contributing to the limited empirical work on crisis-evoked mass revolt in affluent democratic societies.…”
Section: After the Crashmentioning
confidence: 99%
“…For several weeks and months following the bank crash, the unfolding economic crisis had the full attention of the Icelandic media as well as the public. If media attention is essential to mass mobilization (Andrews and Biggs 2006;Klandermans and Goslinga 1996;McCarthy, Smith, and Zald 1996), the Icelandic media paved the way for the protest movement by constantly delivering news and analyses about the alleged local causes of the crisis as well as the country's bleak economic future. The shared national focus on the financial collapse, along with the public's confusion, anxiety, and disappointment, gave public speakers who interpreted the events a tremendous amount of publicity in the media as well as widespread public attention and enthusiasm.…”
Section: Framing Processesmentioning
confidence: 99%
“…A relational approach to social movements can take at least three forms. The most common is the network approach (Snow et al 1980;Klandermans and Oegema 1987;Marwell et al 1988;Gould 1995;Diani and McAdam 2003;Andrews and Biggs 2006). Here, the content of cultural work is refracted through the structure of relationships within which a recruit is embedded.…”
Section: Modes Of Relationships Between Culture and Social Movementsmentioning
confidence: 99%